2013
DOI: 10.1212/wnl.0b013e31829e6f37
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of stroke subtype in vascular risk prediction

Abstract: Patients who survive stroke are at increased risk for NVEs. The risk for NVE varies according to stroke subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Limited infarction was the most common imaging finding. This finding demonstrates a slightly higher prevalence of carotid atherosclerotic disease as a cause for stroke than those previously postulated 2, 20,27 . A more precise elucidation of the role of vulnerable plaques in non-relevant stenosis and their implications in the absence of concurrent brain infarcts detectable on CT remains uncertain.…”
Section: Discussionmentioning
confidence: 38%
“…Limited infarction was the most common imaging finding. This finding demonstrates a slightly higher prevalence of carotid atherosclerotic disease as a cause for stroke than those previously postulated 2, 20,27 . A more precise elucidation of the role of vulnerable plaques in non-relevant stenosis and their implications in the absence of concurrent brain infarcts detectable on CT remains uncertain.…”
Section: Discussionmentioning
confidence: 38%
“…Previously described diagnostic procedures, care methods, and secondary prevention measures [10] were followed, in accordance with the current stroke guidelines, during the hospital admission.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that LAA subtype is associated with a generally increased risk of new vascular events, including both stroke, coronary artery disease and peripheral artery disease. 177,178 Atherosclerosis is a systemic disease and a shared mechanism for coronary artery disease, peripheral artery disease, and atherosclerotic stroke subtype.…”
Section: Vascular Events and Cardiac Diseasementioning
confidence: 99%